Providing a pattern for managing complex mega-projects in the aircraft design and construction industry - Saeed Abdollahi Khoshmardan; Manochehr Manteghi; Abbas Khamseh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: With the research on the country's mega projects, one of the main failure factors in their project management can be sought. Modern aircraft design and construction projects are complex projects known as megaprojects. This research presents a model for managing complex megaprojects in this industry.Methodology: This research is a type of combined research (qualitative-quantitative), and for this purpose, while interviewing aviation experts, the features of aerial mega projects are identified and coded by MAXQDA2020 software, and then the indicators identified in a questionnaire from experts related to the project. Using SMARTPLS3 software, classification and ranking of components and indicators were performed.Findings: In this regard, the designed model has two dimensions, features and management of the megaproject, and 10 main components and 40 indicators were classified and ranked. Finally, the most crucial main component was strategy management.Originality/Value: In this study, considering the importance of aerial projects and the fact that the country has moved towards the design and construction of native birds and several projects in this field have been defined and completed, the characteristics of complex mega projects in the aircraft design and construction industry are determined, and has designed an appropriate model for evaluating the management of complex megaprojects in the aircraft design and construction industry for the first time.